OPTIMASI DESAIN LIGHT SHELF UNTUK DAYLIGHTING BANGUNAN HEMAT ENERGI - , NORMA PRADIPTA, Ir. Jatmika Adi Suryabrata, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The global warming issue and the limitation of unrenewable energy resources create issue of the importance of energy conservation in the building. Solar energy resources in Indonesia has a potency to be used as natural daylighting in building architecture, mostly in high rise building to support saving energy building. Light shelf is one of passive strategies of solar resources utilizing in building. Light shelf has a characteristic to reflect the daylight to the ceiling so that its distribution can be more uniform to the room interior. This research is aimed to find the most optimum light shelf design based on variables that are proceed such as dimension and angle of interior light shelf and also the position of light shelf height that affect on the conventional window dimension ratio to clerestory window as the entrance of daylight into the room. The research was limited to the specified parameter such as location in Jakarta city, office building, time, dimension, and room reflectance and the orientation as the input data in the simulation using DialuxÂ©. Quantity analysis method based on the optimum light criteria by light shelf such as illuminance which fulfill the optimum room standard criteria 200-500 lux, homogenous diffuse and uniformity. The result of the research showed that light shelf effectiveness is influenced by dimension, angle and clerestory window on the light shelf as the most effective design is the the 1,2 m dimension, angle 5o and height 2,0 m or clerestory 0,8 m dimension. The most influential variable is light shelf height or clerestory dimension continued with angle and dimension of light shelf. Light shelf design that recommended is the 0,9-1,2 m dimension, angle 0o-5o and height 2,0 m or clerestory 0,8 m dimension. This recommendation is presented in a prototype formed light shelf mock up.